Inclusão digital de professores : uma proposta de construção de trajetórias personalizáveis em cursos na modalidade a distância - Santos, Pricila Kohls dos (2012)
Nowadays society has been impacted by digital technologies, and we constantly faced out with new forms of interaction regarding Internet and its resources. We argue that teachers must consider the need to acquire communication skills associated with Web 3.0 tools. The society new behavior demands new challengers for educators. The notion of knowledge and how to acquire it also passes such a rethinking process. In this perspective, this research proposes a teachers training course in order to develop digital competencies and skills regarding specific software. In order to achieved our goals and evaluate our methodological proposal, we developed an online course offering customization support, in order to enhance and stimulate learning from participants prior knowledge and short-term goals. The study has qualitative approach, and is also can be characterized as action research. The results showed us a promise set of indicators that allows us to believe that is possible to customize a course using user s feedback. Due Moodle´s restriction it was not possible configure the possibilities in an automatic way. All the personal configurations were done manually. We suggest for future work a join work in order to fulfill this gap. It is expected as a result of this research it is an invitation to reflect on new and / or different ways and possibilities to make the Teacher Training and Distance Learning from the experiences and expectations / experiences of participants in a distance learning course in that time and space of each individual rule is through a methodology that provides for working with the student's prior knowledge as a starting point for building knowledge for the use of technology.